2016
DOI: 10.1038/srep25994
|View full text |Cite
|
Sign up to set email alerts
|

Leaf epidermis images for robust identification of plants

Abstract: This paper proposes a methodology for plant analysis and identification based on extracting texture features from microscopic images of leaf epidermis. All the experiments were carried out using 32 plant species with 309 epidermal samples captured by an optical microscope coupled to a digital camera. The results of the computational methods using texture features were compared to the conventional approach, where quantitative measurements of stomatal traits (density, length and width) were manually obtained. Ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
(41 reference statements)
0
12
0
3
Order By: Relevance
“…[12] discovered that variation in leaf epidermal cell size, shape and thickness form the premise for the taxonomic position of some angiosperm families. More so, [13] revealed that the For the anatomical study of the leaf transverse sections, the principal component analysis revealed that the best descriptors that can be used for easy and correct identification are; epidermal layer, cuticle thickness, epidermal layer thickness, Mesophyll organization, shape of xylem, presence or absence of trichome and trichome type. These characters are diagnostic and can be used in separating the species.…”
Section: Discussionmentioning
confidence: 99%
“…[12] discovered that variation in leaf epidermal cell size, shape and thickness form the premise for the taxonomic position of some angiosperm families. More so, [13] revealed that the For the anatomical study of the leaf transverse sections, the principal component analysis revealed that the best descriptors that can be used for easy and correct identification are; epidermal layer, cuticle thickness, epidermal layer thickness, Mesophyll organization, shape of xylem, presence or absence of trichome and trichome type. These characters are diagnostic and can be used in separating the species.…”
Section: Discussionmentioning
confidence: 99%
“…Stomata are highly characteristics of the leaf epidermis and occupy prominent position on the leaf surfaces. Da Silva et al [19] stated that combining leaf epidermal data with the quantitative stomata data (density, length, and width) can enhance the information concerning species identification. Both the abaxial and adaxial surfaces of A. praecox are characterized by anomocytic stomata which are amphistomatically distributed and are more abundant on the abaxial than the adaxial surface.…”
Section: Discussionmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) and light microscopy (LM) have significant implication for taxonomists to identify morphologically complex species (Da Silva et al, ; Khan, Ullah, Khan, Khan, & Rashid, ; Khan, Ul Abidin, et al, ). Reproductive features of the plants species, as well as floral characters, are considered to provide the most valuable characters to taxonomic affinities (Jones, ; Stace, ) but as the grasses do not flower for a greater part of their life cycle and studies also suggest cuticular features are of great value for the identification, systematics, and phylogenetic relationships of the taxa (Bhatia, ; Jamshed, Ullah, Khan, & Hussain, ; Khan, Ahmad, Zafar, & Ullah, ).…”
Section: Introductionmentioning
confidence: 99%